Hubungan Antara Flexible Working Arrangements dengan Work-Life Balance Pada Karyawan Milenial - Wahyu Tripuspita Sari; Reny Yuniasanti (LPPM Universitas Proklamasi 45, 2025)
This research investigates the relationship between flexible working arrangements and work-life balance among millennial employees. The study purposive sampling method to select 70 millennial employees aged 24-44 years, who have been working for a minimum of 3 months under a flexible working system. Data collection was conducted using a Likert scale. The research utilized two main scales: the Work-life balance scale with a discrimination coefficient ranging from 0.254 to 0.750 and a reliability coefficient of α = 0.834, and the Flexible working arrangement scale with a discrimination coefficient ranging from 0.297 to 0.764 and a reliability coefficient of α = 0.866. Correlation analysis was conducted using Pearson's Product Moment correlation with SPSS Version 22. The results indicate a significant positive relationship between the two variables, with a Pearson correlation coefficient (rxy) of 0.624 and p = 0.000 (p < 0.05). The implications of this research suggest that the implementation of flexible working systems can enhance the work-life balance for millennial employees, ultimately having a positive impact in a dynamic work environment.